Detection of Catalase Activity by Polyacrylamide Gel Electrophoresis (PAGE) in Cell Extracts from Pseudomonas aeruginosa - Pezzoni, Magdalena (2018)
Bacteria in nature and as pathogens commonly face oxidative stress which causes damage to proteins, lipids and DNA. This damage is produced by the action of reactive oxygen species (ROS) such as hydrogen peroxide (H2O2), singlet oxygen, superoxide anion and hydroxyl radical. ROS are generated by antimicrobials, environmental factors (e.g., ultraviolet radiation, osmotic stress), aerobic respiration, and host phagocytes during infective processes. Pseudomonas aeruginosa, a versatile bacterium, is a prevalent opportunistic human pathogen which possesses several defense strategies against ROS. Among them, two catalases (KatA and KatB) have been well characterized by their role on the defense against multiple types of stress. In this protocol, KatA and KatB activities are detected by polyacrylamide gel electrophoresis (PAGE). It is also suggested that the detection of KatB is elusive.